THE REINTERPRETATION OF THE SARMATIAN FINDS FROM THE ROMANIAN PLAIN (I)1 - Vitalie Bârcă (Journal of Ancient History and Archaeology)
Within the pages of this study, the first in the series we aim to accomplish, we analyse a few of the Sarmatian finds in the Romanian Plain (Lehliu, Buzău, Olteniţa-Ulmeni, Vităneşti), which have arisen or still arise debates and for which several chronological frameworks have been suggested. Moreover, the author resumes the discussion of certain aspects related to the Sarmatian presence in the Romanian Plain. Following the analysis of the items in the damaged grave at Lehliu, it was noted that the brooch belongs to a variant dating to the second half of the 1st c. – early 2nd c. AD. Concerning the pendant, it was concluded that the appearance of the rendered character, his sitting position, anthropological type, dress and hairstyle are indicative of the features specific to the eastern populations of Central Asia, including those nomad Iranian. Analogies with the individual’s appearance, sitting position, hairstyle and dress on a series of items, including from the Sarmatian environment, point to a dating in the 1st c. – early 2nd c. AD. Based on such notes, it was reached the conclusion that the two items at Lehliu belonged to an individual in the Sarmatian group arriving from the east into the Danube mouths area, sometime in the second half of the 1st c.AD. Based on the examination of the items in the “hoard” at Buzău, the author concluded they are a very small part of the funerary inventory of a very rich woman’s grave, part of the aristocratic graves of the second half of the 1st c. – early 2nd c. AD from the north-west Pontic area. Furthermore, it was concluded that the grave including these items is from somewhere in the northwest Pontic territory (most likely from the Prut-Dniester interfluve) and by no means from the territory of Buzău county. Last but not least, it was concluded that the items belonged to a woman in the affluent stratum of the Sarmatian society, part of the group of Sarmatians arriving in the north-western area from territories east of Don starting with mid 1st c. AD. In what the dating of this find is concerned, the author pleads for a chronological framing in the second half/last quarter of the 1st c. AD, without yet excluding the end of the 1st c. – early 2nd c. AD. Regarding the casserole, unguentarium and cup at Oltenița-Ulmeni, the author concludes based on the find circumstances, however also on the nearby presence of well datable Sarmatian graves, that very likely, the three items come from one of the damaged graves in 1957. From a chronological point of view, the author argues they were deposited in the grave/graves sometime by mid/ third quarter of the 2nd c. AD, maybe even in the chronological interval comprised between AD 140/150-180, nonetheless, by no means in the second half of the 2st c. AD or the first decades of the 2nd c. AD. The dating of the casserole, unguentarium and cup in this period is also supported by the dating of the objects in G 1 and G 3 in the second half of the 2nd c. AD. According to the author, it is hard to believe that among the graves identified in 1960 and those damaged of 1957, to which most likely belong the mentioned artifacts, there are greater chronological differences, being rather, as suggested by the items’ dating, a contemporary group. Another grave under analysis is that at Vităneşti (T 2 G 2) dated in the specialty literature by the end of the 3rd c. AD, end of the 2nd c. – early 3rd c. AD or in the period previous Trajan’s reign. Upon its analysis, it was concluded that a series of elements and features of the funerary rite and ritual (main burial, large funerary pit, hiding-niche, flat circular ditch surrounding the grave) show that beside the preserved funerary inventory it belongs to the group of graves belonging to the Sarmatian elite in the north and north-west of the Black Sea. This date to the chronological comprised between the second half of the 1st c. AD and the first half of the 2nd c. Concerning the chronological framing of the grave at Vitănești, the author maintains it most likely dates sometime in the first half of the 2nd c. AD. The analysis of the few Sarmatian finds showed they date to a period other than that usually considered. Except for the new dating propositions, the performed analysis also evidenced that some of them (Lehliu, Buzău, Vitănești) are part of a larger group of Sarmatian finds from the north and north-west Pontic area, radically different from the rest of the Sarmatian graves in the same geographical area. Within the graves of this group, a series of elements and features were carried to this area by the novel Sarmatian tribes arriving from the east starting with mid 1st c. AD.